Keys for writers : a brief handbook - Raimes, Ann, 1938- (Boston : Houghton Mifflin Co., 1999)
[This book] provides ... helpful advice for writing and revising, research and documentation, editing and formatting, and grammar and mechanics. -Back cover
Writing process, working with sources: The writing process; Consulting sources, research; MLA documentation; APA, CBE, Chicago documentation; Special writing situations -- Sentence-level issues: Style and sentence review; Common sentence problems; For ESL writers; Punctuation; Format and mechanics -- Glossary of usage; Glossary of grammatic terms
Keywords: English language -- Rhetoric -- Handbooks, manuals, etc; English language -- Grammar -- Handbooks, manuals, etc; Report writing -- Handbooks, manuals, etc